Physical properties of SnO2: Co thin films prepared by chemical spray pyrolysis - Hateef, Areej Adnan (Sulaimani Journal for Pure and Applied Sciences, 2013)
In this research, Co-doped SnO2 thin films were prepared by chemical spray pyrolysis technique using SnCl4.5H2O and CoCl2.6H2O, with impurity percentage are (0%-3%-6%-9%) on glass substrates preheated at (450oC) with spray rate 5sec./1min, and thickness (400nm). The investigation of (XRD) indicates that the (SnO2) films are polycrystalline type of (tetragonal), the optical properties and band gap energy was observed and it`s found varied from (3.361-2.855 eV) when increasing in percentage impurity the energy band gap decreased. The Hall coefficient, concentration and mobility of charge carriers of SnO2:Co films studied, and their results observed that the increase in impurity of cobalt caused increase in electrical properties generally.
Keywords: thin films; SnO2; chemical spray pyrolysis; cobalt